A plausible explanation for male dominance in typhoid ileal perforation - Khan M (Clinical and Experimental Gastroenterology, 2012)
Mohammad KhanDepartment of Microbiology, College of Medicine, Chichiri, Blantyre, MalawiAbstract: The phenomenon of consistent male dominance in typhoid ileal perforation (TIP) is not well understood. It cannot be explained on the basis of microbial virulence, Peyer's patch anatomy, ileal wall thickness, gastric acidity, host genetic factors, or sex-linked bias in hospital attendance. The cytokine response to an intestinal infection in males is predominantly proinflammatory as compared with that in females, presumably due to differences in the sex hormonal milieu. Sex hormone receptors have been detected on lymphocytes and macrophages, including on Peyer's patches, inflammation of which (probably similar to the Shwartzman reaction/Koch phenomenon) is the forerunner of TIP, and is not excluded from the regulatory effects of sex hormones. Hormonal control of host-pathogen interaction may override genetic control. Environmental exposure to Salmonella typhi may be more frequent in males, presumably due to sex-linked differences in hygiene practices and dining-out behavior. A plausible explanation of male dominance in TIP could include sex-linked differences in the degree of natural exposure of Peyer's patches to S. typhi. An alternative explanation may include sexual dimorphism in host inflammatory response patterns in Peyer's patches that have been induced by S. typhi. Both hypotheses are testable.Keywords: explanation, dominance, male, perforation, ileum, typhoid